METODE ISTINBATH HUKUM ZAKAT PROFESI PADA MAJELIS TARJIH MUHAMMADIYAH DAN IMPLIKASINYA TERHADAP PENERAPAN ZAKAT PROFESI DI UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - M.Jamil. Mhd. Syahnan, Ali Baroroh (UIN SU, 2018)
Zakat profession is a problem that has not been discuss in the time of the Prophet Muhammad. However there is no argument in the verses of the Holy Quran and the Prophets Hadith explicitly explain the obligation and unobligation about the law of zakat profession. Causing the differences of opinion among Ulama about its legal status. Meanwhile in Indonesia, Islamic organizations have their respective legal provisions in establishing the law of zakat profession. In this state, Muhammadiyah through Muhammadiyah Tarjih Assembly has set the zakat profession, is a mandatory. This aim of this study is to know the law of zakat profession according to Majelis Tarjih Muhammadiyah and how the method used by Majelis Tarjih Muhammadiyah in establishing the law of zakat profession. And also the fatwaâs implications about application of zakat profession at the University of Muhammadiyah Sumatera Utara. The method that used by writer in this research is descriptive analytical. collecting data from the literature study and field research. This research tried to explains istinbath method of the law of zakat profession from Muhammadiyah organization through Muhammadiyah Tarjih Assembly and fatwa implication to the law of zakat profession applied at University of Muhammadiyah Sumatera Utara.